Behavior of Rhipicephalus sanguineus infestation in dogs from Havana, Cuba - Rodríguez Alonso, María Beatriz (2021)
The behavior of the infestation by Rhipicephalus sanguineus in dogs from three veterinary clinics in Havana was studied between November 2016 and October 2017. In total, 10 533 ticks were collected in 175 of 300 dogs that were examined without discriminating breed, age or sex. In the wet season there was a greater abundance of infestation and a greater number of ticks (p<0.001), greater extent of infestation (p<0.08), and high intensity of infestation (p<0.005). Most of the infested dogs were young, male and of indefined breed. The factors that influenced the behavior of the infestation by R. sanguineus in dogs were breeding and handling.